مصادر سیرت کی تاریخیت پر ابتدائی مغربی تنقیدی رجحانات: Preliminary Western Critical Reflections on Fundamental Sirah Sources - Samia Athar; Dr. Muhammad Feroz-ud-Din Shah (Seerat Studies, 2023)
The academic and scholarly study of Sirah of Hazrat Muhammad (SAW) began in the west during the first half of the 19th century AD when western scholars discovered and edited some manuscripts of fundamental Islamic Sirah sources. However, western writers were not satisfied with these Islamic Sirah sources. They argued that most of the hadith material reflect later developments of Islam and hence must not be used as a historical source for the time of Muhammad (SAW) himself. This skepticism was embraced by several western scholars who were concerned with the original Islamic Sirah sources. As a result, three main groups about Sirah sources came into being. The first group was ready to accept the Islamic traditions as the original Sirah source unless there was any criticism regarding the narrator. The second group rejected the Islamic traditions and emphasized to reconstruct early Islamic history using non-muslim sources. The third group believed in the literary criticism of available Islamic Sirah sources. The article aims to review the skeptical tendencies about Islamic Sirah sources that emerged from time to time in western scholarship.